2020
DOI: 10.1002/ccr3.3428
|View full text |Cite
|
Sign up to set email alerts
|

Involution of classic Kaposi sarcoma lesions under acitretin treatment Kaposi sarcoma treated with acitretin

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“… 24 Interestingly, a case report by Daadaa et al , revealed the efficacy of acitretin as a treatment for KS. 26 However, to our knowledge there is currently no literature available discussing the efficacy of retinoic acid in treating KS with concurrent CTCL.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Interestingly, a case report by Daadaa et al , revealed the efficacy of acitretin as a treatment for KS. 26 However, to our knowledge there is currently no literature available discussing the efficacy of retinoic acid in treating KS with concurrent CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Aditionally, 0.1% alitretinoin is being considered for off-label use in treating non-AIDS related Kaposi's sarcoma (KS), given its reported effectiveness. 19 Although not commonly used in clinical practice, oral acitretin has been successful in treating classic KS unrelated to HIV. 19…”
Section: Kaposi Sarcoma Treatmentmentioning
confidence: 99%
“…19 Although not commonly used in clinical practice, oral acitretin has been successful in treating classic KS unrelated to HIV. 19…”
Section: Kaposi Sarcoma Treatmentmentioning
confidence: 99%
“…Notably, 0.1% alitretinoin is considered for use off-label to treat non-AIDS related KS, based on the documented success [ 275 ]. Oral acitretin has also been used to treat classic KS (unrelated to HIV) successfully, although not typically used clinically [ 276 ].…”
Section: The Use Of Retinoids For Skin Cancer Treatmentmentioning
confidence: 99%